(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
Objective: To determine the effectivity of Plasma enriched with platelets in early knee articular-arthritis Methodology: 125 patients who were added in the study, were of either gender with early knee osteoarthritis (kellgren and Lawrence type 1 and 2) .Patients with traumatic articular-arthritis, grade 3 and 4 articular arthritis, active infection, inflammation or tumour around knee, genu varum & who had an intra articular steroid injection in the last semester were excluded. Informed written consent was taken. Out Patients were chosen and dealt on day care basis. 5cc of Plasma enriched with platelets was introduced into the supra-patellar pouch using sterile measures. Patients were called to revisit at 6th week, 3rd month and 6th month. The clinical evaluation was determined by observation and interviews. End result was assessed by analyzing Western Ontario & Mc Master’s University Osteoarthritis index and Visual Analogue Scale. Findings were put down on a pre-designed Performa and analyzed using SPSS v20. This is a longitudinal case study, conducted at department from July 2017 till June 2019. Results: The average pain score was 17.07 ±3.08SD prior to PRP and decreased to 14.03 ±2.7SD after six months of PRP. The mean score for stiffness was 6.82 ±0.71SD and it decreased to 4.94 ±0.63SD after six months. The mean functional outcome score decreased from 58.57 ±2.29SD to 48.02 ±1.51SD. The comparison of the means before and after PRP showed significant results (p<0.01). Six months following injection, 49.6% (62 patients) were evaluated as having a satisfactory outcome (VAS 1-4),38 patients (30.4%) had a satisfactory outcome (VAS 5 to 7) whereas 25 individuals (20%) had a poor outcome (VAS 8-10). Conclusion: Plasma enriched with platelets is an easy, inexpensive and less invasive procedure to cure early-stage progressive lesions of cartilage of knee-joint with minimal or no adverse-effects & has benefits in terms of relief from pain, patient contentment and improvement in knee range of motion & quality of life.